Controllability of Linear Discrete-Time Systems with Both Delayed States and Delayed Inputs - Hong Shi; Guangming Xie; Wenguang Luo (Abstract and Applied Analysis)
The controllability issues for discrete-time linear systems with delay in state and control are addressed. By introducing a new concept, the controllability realization index (CRI), the characteristic of controllability is revealed. An easily testable necessary and sufficient condition for the controllability of discrete-time linear systems with state and control delay is established.